Thoracic Epidural Abscesses: A Systematic Review. Issue 4 (December 2018) - Howie, Benjamin A.; Davidson, Iyooh U.; Tanenbaum, Joseph E.; Pahuta, Markian A.; Buchholz, Avery L.; Steinmetz, Michael P.; Mroz, Thomas E.
Study Design: Systematic review. Objectives: Past research has demonstrated increased speed and severity of progression for spinal epidural abscesses (SEAs) of the thoracic level, specifically, when compared with SEAs of other spinal cord levels. Untreated, this infection can result in permanent neurological sequelae with eventual progression to death if inadequately managed. Despite the seriousness of this disease, no articles have focused on the presentation, diagnosis, and treatment of SEAs of the thoracic level. For this reason, specific focus on SEAs of the thoracic level occurred when researchers designed and implemented the following systematic review. Methods: A query of Ovid-Medline and EMBASE, Cochrane Central, and additional review sources was conducted. Search criteria focused on articles specific to thoracic epidural abscesses. Results: Twenty-five articles met inclusion criteria. The most commonly reported symptoms present on admission included back pain, paraparesis/paraplegia, fever, and loss of bowel/bladder control. Significant risk factors included diabetes, intravenous drug use, and advanced age ( P = .001). Patients were most often treated surgically with either laminectomy, hemilaminectomy, or radical decompression with debridement. Patients who presented with neurological deficits and had delayed surgical intervention following a failed antibiotic course tended to do worse compared with their immediate surgical management counterparts ( P < .005). Conclusions: For the first time researchers have focused specifically on SEAs of the thoracic level, as opposed to previously published general analysis of SEAs as a whole. Based on the results, investigators recommend early magnetic resonance imaging of the spine, laboratory workup (sedimentation rate/C-reactive protein, complete blood count), abscess culture followed by empiric antibiotics, and immediate surgical decompression when neurological deficits are present.